2023
DOI: 10.3390/md21080430
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced In Vitro Anti-Photoaging Effect of Degraded Seaweed Polysaccharides by UV/H2O2 Treatment

Abstract: The high molecular weight and poor solubility of seaweed polysaccharides have limited their function and application. In this study, ultraviolet/hydrogen peroxide (UV/H2O2) treatment was used to prepare low-molecular-weight seaweed polysaccharides from Sargassum fusiforme. The effects of UV/H2O2 treatment on the physicochemical properties and anti-photoaging activity of S. fusiforme polysaccharides were studied. UV/H2O2 treatment effectively degraded polysaccharides from S. fusiforme (DSFPs), reducing their mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…UVB exposure induces oxidative stress in keratinocytes [19], and increased production of ROS is deleterious to keratinocytes [19]. However, previously, peptides from seaweed [20], a frog peptide [16], and a porcine placenta peptide [17] were reported to prevent the photoaging of skin by inhibiting ROS accumulation. Also, a peptide from tilapia gelatin hydrolysate inhibited ROS production by enhancing the levels of antioxidant factors superoxide (SOD) and glutathione (GSH) in UVB-irradiated HaCaT cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…UVB exposure induces oxidative stress in keratinocytes [19], and increased production of ROS is deleterious to keratinocytes [19]. However, previously, peptides from seaweed [20], a frog peptide [16], and a porcine placenta peptide [17] were reported to prevent the photoaging of skin by inhibiting ROS accumulation. Also, a peptide from tilapia gelatin hydrolysate inhibited ROS production by enhancing the levels of antioxidant factors superoxide (SOD) and glutathione (GSH) in UVB-irradiated HaCaT cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…Our research group previously found that ultraviolet/hydrogen peroxide (UV/H 2 O 2 ) treatment could be used to degrade marine polysaccharides. For example, it could effectively reduce the molecular weight of Sargassum fusiforme polysaccharide and enhance its anti-inflammatory and anti-photoaging activities [10,11]. Whether the UV/H 2 O 2 treatment could degrade fucoidan and improve its activity needs to be explored.…”
Section: Introductionmentioning
confidence: 99%